Foreign language listening anxiety among French language learners in Malaysia - Majunggi, Jenniesy; Abdul Halim, Hazlina (Human Resource Management Academic Research Society, 2021)
Foreign Language Listening Anxiety (FLLA) has a considerable impact on students' foreign language learning achievements. The feeling of tension and apprehension while listening to a foreign language could be caused by various factors, namely the teachers, the learners themselves or even the classroom atmosphere (Pan, 2016). Using Kim's (2000) Foreign Language Listening Anxiety Survey (FLLAS), this study investigates whether French language students in Secondary Schools suffer from listening anxiety as well as the causes of their anxieties in listening comprehension. The FLLAS survey had been distributed to 36 SMK Elopura French language students. The survey’s findings show that students experience a high level of anxiety in French language listening. This research will attempt to identify the learners’ anxiety level and explain the cause that triggers their listening anxiety.